‘I’m getting out to nothing’: A temporal analysis of dominant discourses and practices with residents convicted of child sex offences in probation Approved Premises - Roberts, Nicola (Probation journal, 2024)
People convicted of child sex offences are viewed as a dangerous and demonised offender group, yet little research has considered their resettlement post-residency from Approved Premises. Using data from two qualitative studies carried out 15 years apart, we explore what changes there have been in the discourses and practices with residents convicted of child sex offences. The authors found that whilst rehabilitation and resettlement were contemporarily considered as more holistic endeavours, the primary function of the Approved Premises remains managing the risks of residents convicted of child sex offences. Most significantly, this hindered their social integration into the community.